PENGARUH KOMPETENSI TERHADAP KINERJA PEGAWAI PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KABUPATEN MAMUJU UTARA - Rande, Dina (Katalogis, 2016)
The aim of this study; (1) to identify and analyze the effect on employee performance competence simultaneous Department of Transportation, Communications and Information Technology of North Mamuju regency; (2) to identify and analyze the effect of a partial competence on the performance of staff at the Department of Transportation, Communications and Information Technology of North Mamuju regency. This type of research with a quantitative approach of this research is descriptive and quantitative. Population research staff at the Department of Transportation, Communications and Information Technology of North Mamuju regency totaling 38 people who were taken using census techniques so that all the population sampled. Data were analyzed using linear regression. The results showed; (1) the influence of competence simultaneously on the performance of staff at the Department of Transportation, Communication and Information Mamuju Utara determined by motives (motives), properties (traits), the concept of self (self-concepts), knowledge (knowledge) and skills (skills) , Great influence on the performance of employee competence is 78.9% with the level of competence of the relationship between employee performance "very strong". It means that the rise of competence, it will improve the performance of employees in the Department of Transportation, Communications and Information Technology of North Mamuju regency; (2) the influence of competency partially on the performance of employees of the Department of Transportation, Communication and Information Mamuju Utara determined by motives (motives), properties (traits), the concept of self (self-concepts), knowledge (knowledge) and skills (skills) .As results descriptive statistics shows the dimensions properties (traits) to obtain persentasetinggi, while the lower dimensions are knowledge and skill.